Functional connectivity of the angular gyrus in normal reading and dyslexia - Horwitz, B. (National Academy of Sciences, 1998)
The classic neurologic model for reading, based on studies of patients with acquired alexia, hypothesizes functional linkages between the angular gyrus in the left hemisphere and visual association areas in the occipital and temporal lobes. The angular gyrus also is thought to have functional links with posterior language areas (e.g., Wernicke’s area), because it is presumed to be involved in mapping visually presented inputs onto linguistic representations. Using positron emission tomography , we demonstrate in normal men that regional cerebral blood flow in the left angular gyrus shows strong within-task, across-subjects correlations (i.e., functional connectivity) with regional cerebral blood flow in extrastriate occipital and temporal lobe regions during single word reading. In contrast, the left angular gyrus is functionally disconnected from these regions in men with persistent developmental dyslexia, suggesting that the anatomical disconnection of the left angular gyrus from other brain regions that are part of the “normal” brain reading network in many cases of acquired alexia is mirrored by its functional disconnection in developmental dyslexia.